SARS-CoV-2 infection: advocacy for training and social distancing in healthcare settings. Issue 3 (November 2020) - Gagneux-Brunon, A.; Pelissier, C.; Gagnaire, J.; Pillet, S.; Pozzetto, B.; Botelho-Nevers, E.; Berthelot, P.
SUMMARY: This article reports the observed rate of infection with severe acute respiratory syndrome coronavirus-2 in healthcare workers (HCWs) who worked on wards dedicated to care of patients with coronavirus disease 2019 (COVID-19) compared with HCWs who worked on non-COVID-19 wards. The infection rate was significantly higher among HCWs who worked on non-COVID-19 wards (odds ratio 2.3, P =0.005), illustrating the need to strengthen social distancing measures and training.